2017
DOI: 10.1177/2047487316687104
|View full text |Cite
|
Sign up to set email alerts
|

Community-based prevalence study of rheumatic heart disease in rural Ethiopia

Abstract: Background Chronic Rheumatic Heart disease (RHD) continues to be a health problem in many low and middle income countries and especially in sub-Saharan Africa. Echocardiography has shown that the disease is far more widespread than may be detected by clinical assessment, but data are lacking on the prevalence and epidemiological features in rural Africa. Design Community-based prevalence survey Methods We used transthoracic echocardiography to carry out a population-based study of RHD in a rural area of Ethiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 26 publications
4
55
1
Order By: Relevance
“…Rheumatic fever remains the major cause of mitral valve (MV) stenosis, particularly in developing countries . Rheumatic inflammation of the endocardium predisposes to multiple gross changes in the mitral valve, including commissural fusion with reduction in the diastolic mitral valve opening .…”
Section: Introductionmentioning
confidence: 99%
“…Rheumatic fever remains the major cause of mitral valve (MV) stenosis, particularly in developing countries . Rheumatic inflammation of the endocardium predisposes to multiple gross changes in the mitral valve, including commissural fusion with reduction in the diastolic mitral valve opening .…”
Section: Introductionmentioning
confidence: 99%
“…As was shown in a community-based screening in Ethiopia,4 the prevalence of RHD increased with age across the paediatric population, peaking in those between 16 years and 20 years. In this age group, 1.34% (95% CI 0.59% to 3.5%) of those screened had definite RHD and 4.84% had either definite or borderline RHD (95% CI 2.89% to 7.53%).…”
Section: Discussionmentioning
confidence: 58%
“…Of the studies that have been conducted among adults, none have looked at participants beyond 35 years of age, even though our data suggest that the highest prevalence may be found in members 41–50 years of age, and none have assessed prevalence across the lifespan in a single population. Furthermore, the literature’s focus on children in schools potentially leads to biased estimates of RHD, which emerging evidence suggests could be more common among children too ill or poor to attend school 4. The present study thus advances the literature on RHD prevalence in three several important dimensions: use of survey sampling techniques to ensure representative populations, focus on communities rather than schools and inclusion of adults and children within the same population.…”
Section: Discussionmentioning
confidence: 81%
“…Other evidence in support of the hypothesis includes a historic outbreak of ARF that followed an outbreak of scabies in Trinidad in the late 1970s . Two other studies have shown a positive association between echocardiographic evidence of rheumatic heart disease and a history of treatment for scabies …”
mentioning
confidence: 92%
“…Recent studies have drawn attention to a link between ARF or rheumatic fever incidence and scabies . This evidence includes a record linkage study conducted by our research group and a case–control study (yet to be published) .…”
mentioning
confidence: 99%